TRANSFORMASI GARAP GENDING CUCUR BAWUK KE DALAM MUSIK CAMPURSARI KELOMPOK BALISA - Heri Prasetyo; Muhammad Nur Salim (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2019)
The transformation of garap music into campursari music of the Balisa group in Sragen was motivated by the phenomenon of garap transfer from traditional musical karawitan into campursari musical form. This garap transition is a creative way for Balisa members to work on garap gending, one of which is Gendhing Cucur Bawuk into campursari music. The creative process that occurs in the elements of working on music is manifested in the stages in transforming the processing of gending. The transformation process of gending is influenced by several supporting factors. To answer this problem, the author uses the concept of garap and is supported by thoughts about transformation. This research uses a qualitative methodology, by conducting observations, interviews and literature studies so that information or related data are obtained. The purpose of this study was to determine the process of transformation of music production that occurred in the Balisa Campursari group. The results showed that the transformation of music production in the Campursaari Balisa group went through several stages such as instrument adjustment, laras adjustment, and style adjustment. The factors that support this transformation process are determined by the “penggarap”, garap determinant and garap consideration.Keywords: transformation, campursari music, garap gending.